GLYCEMIC INDEX OF STARCH-BASED FOODS COMMONLY CONSUMED IN TERENGGANU, MALAYSIA - ABU BAKAR, NUR AIN FATINAH; ABD RASHID, AINAA ALMARDHIYAH; ISHAK, MOHD FATAHUDIN; MHD JALIL, ABBE MALEYKI (Malaysian Applied Biology, 2019)
This study was aimed to determine the GI of nine starch-based foods commonly consumed in Terengganu, Malaysia as follows: noodles (fried yellow mi, fried mihun, fried kuay teow), local kuih (akok, apam ayu, mek comel), and local fish snacks (boiled keropok lekor, fried keropok lekor, fried keropok keping). Glycemic index determination was done according to standard GI protocol. Ten healthy subjects completed each category of starch-based foods. i.e. three test foods and one reference food after an overnight fast (10-12 hr). Capillary blood samples were measured at baseline (fasting, 0 min) and at 15, 30, 45, 60, 90 and 120 min thereafter. Glycemic index was determined by expressing the percentage incremental area under the curve of the test food over reference food (glucose). Four foods were categorized as low GI as follows: fried keropok keping, GI = 29.00 (7.5); fried mihun, GI = 45.40 (7.43); akok, GI = 49.34 (5.11) and fried yellow mi, GI = 49.56 (6.77). These foods had significantly lower GI than reference food (glucose; GI = 100) (p < 0.05). The remaining five foods were categorized as high GI as follows: apam ayu, GI = 90.56 (12.0), mek comel; GI = 82.71 (9.42); fried kuay teow, GI = 79.50 (9.34); boiled keropok lekor, GI = 79.00 (9.50) and fried keropok lekor, GI = 70.00 (13.40). This study shows that starch-based foods raised glucose response differently and depends on the factors such as nutrient composition, food structure, processing techniques and cooking methods.